The phenomenon of Islamic learning organization: choosing an appropriate qualitative method - Al-Qolaq, Ammar; Sharif, Mohmad Yazam (2016)
The objective of this paper is argue the possible qualitative method to undertake a study on a new phenomenon called the "Islamic Learning Organization" (ILO). An earlier paper was presented in an international conference in Kazakhstan in July 2015 discussing the conceptualization of ILO. To implement the study since the concept is considered new, the qualitative approach is deemed suitable.The question is what qualitative method should be chosen. The author viewed that a case study design should be selected and the in-depth interview would be the main data collection method.